Istorijsko iskustvo o opsadi i odbrani grada Olova / Historical Experience of Siege and Defense of the Town Olovo: 1992–1995 / 1992-1995 - Pejanović, Mirko (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
There are few studies that, on the basis of relevant documents, fully illuminate the resurgence of resistance and defenses in municipalities and cities in the territory of Bosnia and Herzegovina during the 1992-1995 war. One of these books was authored by Prof. Dr. Rasim Muratović. The research study under the title Olovo 1992-1995 – Stradanje i razaranje herojskog Olova (Olovo 1992-1995 – Devastation and Destruction of a Hero Town) contains a historical overview and empirical facts about the widespread participation of the Municipality of Olovo inhabitants in the defense of their local community from the irredentist Greater Serbia plan to take up this space in order to establish a corridor between the Romanija-Ozren-Doboj area. The fallen ones in the defense of the town of Olovo, the fight for freedom and gained defense experience have a special place in establishing the truth about the power of the Bosnian man to fight for the sovereignty and integrity of the state of Bosnia and Herzegovina.